If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -9x = 22 Reorder the terms: -9x + y = 22 Solving -9x + y = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -9x + y + -1y = 22 + -1y Combine like terms: y + -1y = 0 -9x + 0 = 22 + -1y -9x = 22 + -1y Divide each side by '-9'. x = -2.444444444 + 0.1111111111y Simplifying x = -2.444444444 + 0.1111111111y
| 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x | | y=7500-9.5(8000) | | y=7500-9.5(10000) | | 25m=75 | | y=75000+9.5x | | 27+8=10 | | 4(C-9)C=15 | | 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 | | c-14=6 | | 6(10x-13)=222 | | -12/3x-41/7 | | 16-s=20 | | -6+w/3=-8 |